ANALISIS PUTUSAN LEPAS DARI TUNTUTAN HUKUM TERHADAP PELAKU TINDAK PIDANA KORUPSI BERDASARKAN PUTUSAN PENGADILAN NEGERI PUTUSIBAU NOMOR 57/Pid.B/2010/PN.PTSB - IMAM RIYADI, S.Ik. A.21210044, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
AbstractThis thesis is studies of Decision Analysis Gets Out Of Prosecution To Corruption Crime Perpetrator Based On Putusibau District Court Decision Number 57/Pid.B/2010/PN.PTSB. By the legal reseach method, obtained conclusion that : 1. Based on second assertion of publik procecutor, deed of defendant Ir. AM. YUHASDI, 53 Years, Civil Public Servant on Constructs Genera and Irrigation Agency Kapuas Hulu Region, has fulfilled all element Section 3 Law Number 31, 1999 as has been changed and added with invitors Law Number 20, 2001 About Eradication of Corruption Crime. But by Ceremony Of Judge Of District Court Putusibau according to decision Nomor : 57/Pid.B/2010/PN.PTSB, the simply is broken gets out of prosecution, with reason of though defendant has proven validly and assures according to law to do a deed, but the deed is assessed